L2 feelings through interaction in a Japanese-English online chat exchange. Issue 2 (15th March 2021) - Sampson, Richard James; Yoshida, Reiko
ABSTRACT: Purpose: Communication technology is used in diverse ways in our everyday lives. This research aims to fill a gap in research into L2 learner psychology connected with using online communication tools such as messaging platforms. Approach: The article focuses on practitioner research into feelings experienced during online L2 text chat. Twenty-one undergraduates studying English as a Foreign Language at a university in Japan, and nineteen Japanese as a Foreign Language undergraduates from a university in Australia participated. In chat sessions, learners had thirty minutes interacting in their first language, and thirty minutes with their second language. Longitudinal, qualitative data was collected over the seven-week exchange through reflective session reports. Findings: Analysis uncovered seven positively- and four negatively-valenced feelings experienced through L2 online chat. In both the EFL and JFL groups, mentions of positive amounted to more than double those of negative emotions. These feelings connected with various object-foci such as topics about culture, differences in life experiences, hobbies, linguistic aspects of the L2, L2 identity, chat partners and the chat process itself. Originality: The article builds on existing research by adding greater qualitative detail to understandings of feelings emergent through online L2 learning.